Specific Cell Wall Proteins Confer Resistance to Nisin upon Yeast Cells - Dielbandhoesing, S. K. (American Society for Microbiology, 1998)
The cell wall of a yeast cell forms a barrier for various proteinaceous and nonproteinaceous molecules. Nisin, a small polypeptide and a well-known preservative active against gram-positive bacteria, was tested with wild-type Saccharomyces cerevisiae. This peptide had no effect on intact cells. However, removal of the cell wall facilitated access of nisin to the membrane and led to cell rupture. The roles of individual components of the cell wall in protection against nisin were studied by using synchronized cultures. Variation in nisin sensitivity was observed during the cell cycle. In the S phase, which is the phase in the cell cycle in which the permeability of the yeast wall to fluorescein isothiocyanate dextrans is highest, the cells were most sensitive to nisin. In contrast, the cells were most resistant to nisin after a peak in expression of the mRNA of cell wall protein 2 (Cwp2p), which coincided with the G2 phase of the cell cycle. A mutant lacking Cwp2p has been shown to be more sensitive to cell wall-interfering compounds and Zymolyase (J. M. Van der Vaart, L. H. Caro, J. W. Chapman, F. M. Klis, and C. T. Verrips, J. Bacteriol. 177:3104–3110, 1995). Here we show that of the single cell wall protein knockouts, a Cwp2p-deficient mutant is most sensitive to nisin. A mutant with a double knockout of Cwp1p and Cwp2p is hypersensitive to the peptide. Finally, in yeast mutants with impaired cell wall structure, expression of both CWP1 and CWP2 was modified. We concluded that Cwp2p plays a prominent role in protection of cells against antimicrobial peptides, such as nisin, and that Cwp1p and Cwp2p play a key role in the formation of a normal cell wall.